PENGARUH MINAT BELI PAKAIAN, PERILAKU PEDAGANG, KEPUASAN KONSUMEN TERHADAP KUALITAS HIDUP MASYARAKAT LOKAL KABUPATEN ENDE - Damianus Tola; Helena Rosalia Parera; Sayful Amrin (Bajang Institute, 2021)
This study aims to determine the effect of clothing buying interest, merchant behavior, consumer satisfaction on the quality of life of the local community in Ende. This type of research is descriptive quantitative research. The sampling technique used purposive sampling, while primary data collection used questionnaires and secondary data used documentation. And data analysis using multiple regression analysis. The results of the study partially and simultaneously show that there is a significant influence between interest in buying clothes, merchant behavior, satisfaction with the quality of life of the community with and R Square value of 0.735 or 73.5 percent while the remaining 26.5 percent influenced by other variables not disclosed in this research model.